1982
DOI: 10.1002/cne.902070110
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative electron microscopic analysis of the optic nerve of the turtle, Pseudemys

Abstract: It is estimated by means of electron microscopy that the optic nerve of the turtle Pseudemys scripta elegans contains 394,900 fibers of which approximately 80% are myelinated. The total fiber count agrees well with counts obtained from electron microscopic studies on other turtle species. There are, however, differences among these species in the percentage of myelinated fibers in the optic nerve. The axon diameter distribution of the myelinated fibers (excluding myelin) has a mode at 0.87 micrometer while tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…Our estimate of 405,235 optic nerve fibers in the chameleon is comparable to that of Pseudemys [395,000 fibers; Geri et al, 1982], greatly exceeds those of Vipera [59,000 fibers; Ward et al, 1989] and Clemmys [302,000 fibers; Davydova et al, 1982], but is lower than that of Ctenophorus [827,000 fibers; Beazley et al, 1997]. There are, however, notable differences in the percentage of myelinated fibers between these species and the chameleon, and indeed within the chameleon itself, in which the percentage rises from 25% close to the eyeball to 60% in proximity to the chiasma.…”
Section: Optic Nerve Fiber Countssupporting
confidence: 57%
See 3 more Smart Citations
“…Our estimate of 405,235 optic nerve fibers in the chameleon is comparable to that of Pseudemys [395,000 fibers; Geri et al, 1982], greatly exceeds those of Vipera [59,000 fibers; Ward et al, 1989] and Clemmys [302,000 fibers; Davydova et al, 1982], but is lower than that of Ctenophorus [827,000 fibers; Beazley et al, 1997]. There are, however, notable differences in the percentage of myelinated fibers between these species and the chameleon, and indeed within the chameleon itself, in which the percentage rises from 25% close to the eyeball to 60% in proximity to the chiasma.…”
Section: Optic Nerve Fiber Countssupporting
confidence: 57%
“…However, the percentage of myelinated fibers found close to the chiasma in our material [60%] is similar to that reported for Emys [53%; Davydova et al, 1982], is considerably greater than the percentage reported by the same authors for Clemmys (29%), Agrionemys (10%) and Testudo (10%). In Pseudemys [90%; Geri et al, 1982] and Vipera [83%; Ward et al, 1989], on the other hand, the percentage is considerably higher. These observations demonstrate that the composition of the reptilian optic nerve shows a great degree of interspecific variation.…”
Section: Optic Nerve Fiber Countsmentioning
confidence: 99%
See 2 more Smart Citations
“…OLGs have been intensely studied in mammals but not in nonmammalian species because, unlike astrocytes that express glial fibrillary acid protein (GFAP) throughout the vertebrate phylogenetic line, molecular heterogeneity has been reported for vertebrate OLGs (Birling and Nussbaum, 1995;Birling et al, 1995;Anderson et al, 1999). Electron microscopic studies in the turtle have demonstrated that the animals possess macroglial cells that are similar to those found in mammals (Geri et al, 1982;Rainey and Ulinski, 1982;Davila et al, 1987), and recent studies have described GFAP and vimentin expression in astrocytes (Kalman et al, 1997;Lazzari and Franceschini, 2006). However, while a few studies have demonstrated OLGs and myelination in the developing and adult reptile brain, little is known about the immunohistochemical detection of OLGs in the reptile nervous system (Birling and Nussbaum, 1995;Monzón-Mayor et al, 1998;Romero-Aleman Mdel et al, 2003;Santos et al, 2006).…”
Section: Introductionmentioning
confidence: 85%